Efficient monopolies : the limits of competition in the European property insurance market - Ungern-Sternberg, Thomas von. (Oxford ; New York : Oxford University Press, 2004)
This book studies the market for property insurance in five countries, Britain, Spain, France, Switzerland and Germany.It argues that in this market state monopolies outerperform competitive markets.
Includes bibliographical references (p. [152]-155) and index.
aia 07/05/13
Loan
Keywords: Monopolistic competition; Monopolistic; Property insurance; Efficient monopolies